THE HERO CREATION SKILLS OF XUDOYBERDI TO‘XTABOYEV (Scientific journal of the Fergana State University, 2025)
This article tells about the folk art of the Uzbek people Khuduvchis Khudoyberdi Tukhtaboevning, the hero and hero of yaratishdag. This verse says that people living in Madinah have the right to participate in jihad, but do not have the right to participate in jihad. An artist working in Hossa zhihatlar's uziga, Hossa zhihatlar's skill and art style helped him.